Financial accounting and corporate governance: a discussion - Sloan, Richard G. (Journal of Accounting and Economics, 2001)
Bushman and Smith (2001, this issue) provide a useful review of research on the role of accounting in management compensation contracts and an appealing future research agenda that builds on recent research using a cross-country approach. This paper rounds out their discussion by highlighting some limitations of their research agenda, providing a critical review of the contributions of accounting scholars to governance research and highlighting research opportunities on the role of financial accounting in governance mechanisms other than managerial incentive contracts.